Anthropology of Education and the Understanding of Cultural Diversity - Drozdowicz, Jarema (Atiner, 2016)
Anthropology of education is regarded as a relatively new sub discipline combining theory and methods of anthropological and ethnographic studies with those of pedagogy and educational studies. This paper deals with the problem how the anthropology of education and also anthropology in general might be applied towards the issue of cultural diversity and the category of cultural difference. It is important to NATO that those problems gain a new meaning and seem to be crucial in the context of the transformation that occurs today in Western societies. This very change could be described as the transition of the nation state into a multicultural state and society. The debate surrounding the idea and praxis of multiculturalism raises further questions on how we are able to create patterns of integration applied to minorities, migrants, refugees etc. In the light of the recent processes and events in Europe this question seems to be significant more than ever and the anthropology of education could serve here as a partial answer to the raised issues.
Keywords: anthropology of education; educational ethnography; education; multiculturalism; diversity; cultural difference